Blood pressure estimation by pulse wave velocity measurement using conventional pulse oximeter. - Harry Suhardi. (2013)
Pulse Oximeter is a device that allows monitoring of pulse rate and blood oxygenation percentage in the artery by non-invasive means. It can be used to detect pulse propagation through the arterial vessel, the speed of which is called Pulse Wave Velocity (PWV). Pulse Wave Velocity has become an important factor in determining the arterial stiffness and for risk evaluation. To be able to calculate PWV, Pulse Transit Time (PTT) between two points on the limb, one being proximal and the other distal, has to be determined. There are many different techniques of determining reference point in plethysmography waveform with different algorithms, among which, two popular techniques will be introduced in this report. Systolic Blood Pressure (BP) estimation can also be performed using PTT or PWV value, by using Moens-Kortweg equation to relate BP to PTT or PWV. This method of BP estimation can provide a non-invasive and yet continuous BP values. This paper focuses on determining PTT value by just using conventional Pulse Oximeter; NONIN OEM III Evaluation Kit. This method ensures a cost-effective method of measuring PWV and determining systolic BP value from PWV value.